PENGARUH FRAUD PENTAGON DAN CORPORATE GOVERNANCE TERHADAP FINANCIAL STATEMENT FRAUD BENEISH MODEL - Vicky Yuvin; Partogian Sormin (Fakultas Ekonomi Universitas Tarumanagara, 2022)
This study aims to obtain evidence related to the effect of fraud pentagon theory and corporate governance on financial statement fraud. This study is conducted by selecting a sample of a manufacturing company which is listed on the Indonesia Stock Exchange in year 2014 – 2018. The samples obtained are 450 data. The independent variable in this study is the fraud pentagon which are consist of pressure, opportunity, rationalization, competence, arrogance also corporate governance variables. This study uses multiple linear regression analysis and is processed by using IBM SPSS 22 software. The result of this study partially indicates that pressure, opportunity, rationalization, arrogance and corporate governance variables have no positive effect on financial statement fraud. While the competence variabel has a positive effect on financial statement fraud.